2019
DOI: 10.1016/j.compscitech.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of state of charge on elastic properties of 3D structural battery composites

Abstract: The effects of state of charge (SOC) on the elastic properties of 3D structural battery composites are studied. An analytical model based on micromechanical models is developed to estimate the effective elastic properties of 3D structural battery composite laminae at different SOC. A parametric study is performed to evaluate how different design parameters such as volume fraction of active materials, stiffness of constituents, type of positive electrode material, etc. affect the moduli of the composite lamina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 26 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…In earlier work by the authors [21] the state of charge was shown to have a significant effect on the elastic properties of this type of material. In that study, only extremes in SOC were considered and thermal effects were neglected.…”
Section: Elastic Propertiesmentioning
confidence: 89%
See 3 more Smart Citations
“…In earlier work by the authors [21] the state of charge was shown to have a significant effect on the elastic properties of this type of material. In that study, only extremes in SOC were considered and thermal effects were neglected.…”
Section: Elastic Propertiesmentioning
confidence: 89%
“…The objective of this paper is to study the internal stresses in a 3D structural battery composite caused by heat generation and volume change of constituents under galvanostatic cycling (constant current charge/discharge cycles). A semi-analytical framework has been developed to predict the internal stresses based on a concentric cylinder (CC) model [20,21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Carlstedt et al (2019b) developed an analytical model to investigate how the elastic properties of the 3D-fibre structural battery composite are affected by changes in volume and stiffness of the constituents associated with a change in SOC. Carlstedt et al (2019b) present results from a parametric study performed to analyse how different design parameters such as volume fraction of active materials, stiffness of constituents, type of positive electrode material, etc affect the moduli of the structural battery composite for extremes in SOC. Indeed, the composite's transverse elastic properties E T and G TT and the in-plane shear modulus G LT were found to be highly affected by the SOC for critical configurations, while the longitudinal stiffness E L was not.…”
Section: Modellingmentioning
confidence: 99%